Stable mixed hematopoietic chimerism permits tolerance of vascularized composite allografts across a full major histocompatibility mismatch in swine. (28th August 2014) - Mathes, David W.; Solari, Mario G.; Gazelle, Guy Scott; Butler, Peter E. M.; Wu, Anette; Nazzal, Adam; Nielsen, Gunnlauger P.; Huang, Christene A.; Sachs, David H.; Lee, Wei Ping Andrew; Randolph, Mark A.
Summary This study tested the hypothesis that vascularized composite allografts (VCA) could be accepted in a robust model of hematopoietic chimerism by injecting allogeneic bone marrow cells (BMC) into swine fetuses. Outbred Yorkshire sows and boars were screened to ensure the absence of the major histocompatibility (MHC) allele SLAcc of inbred MGH miniature swine and then mated. Bone marrow harvested from an SLAcc swine donor was T‐cell depleted and injected intravenously into the fetuses between days 50–55 of gestation. After birth, the piglets were studied with flow cytometry to detect donor cells and mixed lymphocyte reactions (MLR) and cell‐mediated lympholysis (CML) assays to assess their response to donor. Donor‐matched VCAs from SLAcc donors were performed on four chimeric and two nonchimeric swine. The results showed donor cell engraftment and multilineage macrochimerism after the in utero transplantation of adult BMC, and chimeric animals were unresponsive to donor antigens in vitro. Both control VCAs were rejected by 21 days and were alloreactive. Chimeric animals accepted the VCAs and never developed antidonor antibodies or alloreactivity to donor. These results confirm that the intravascular, in utero transplantation of adult BMC leads to donor cell chimerism and donor‐specific tolerance of VCAs across a full MHC barrier in this animal model.